Demand for Skills : Main Results of the Azerbaijan STEP Employer Survey - Rutkowski, Jan J. (World Bank, Washington, DC, 2015)
This note summarizes the main findings of the STEP Employer Skills Survey carried out in Azerbaijan in 2013. The note argues that there is a skills shortage in Azerbaijan. Azeri employers claim that it is difficult to find workers with required skills. The shortage is particularly pronounced in the case of modern, innovative firms, which tend to required more advanced skills. The education system does not meet the needs of the majority of employers. In particular, it does not equip young workers with the practical skills that are required in the workplace, and with knowledge that is up-to-date. The note finds that employers seek not only technical, job-specific skills but also cognitive skills (such as literacy, numeracy and problem solving) and adequate socio-behavioural skills (such as communication, teamwork, leadership and ability to work independently). Conscientiousness stands out as a personality trait that is critical for employability. Unfortunately, many young job applicants lack the skills demanded by employers. The key employability skills that young workers are most frequently lacking include job-specific technical skills, problem solving skills, communication, teamwork and leadership skills. Hence, the skills gap refers not only to technical skills but also to higher-order cognitive skills and socio-behavioural skills. By their nature, these results show subjective perceptions of employers. And these perceptions reflect not only the objective conditions, but also employers’ expectations regarding worker skills that may be excessive. Nonetheless the results signal a skill problem in Azerbaijan, and employers’ criticism of the quality and relevance of education should not be too easily disregarded. The survey’s results strongly suggest that the quality of education needs to be improved, and the education system needs to be more responsive to labor market needs in order to support growth and modernization of the Azerbaijan’s economy.